Application of hybrid polymer as two dimensional grating and it’s lasing characteristic - Sahrul Hidayat,; Pitriana .P,; Hidayat .R,; Fitrilawati,; Bahtiar .A,; Siregar .R.E,; Ozaki .M, (Universiti Kebangsaan Malaysia, 2011)
A two dimensional grating has been fabricated from hybrid polymer incorporated with organic dye-laser. The precursor hybrid polymers were synthesized from TMSPMA by sol-gel method. The precursor was mixed with photo-initiator to make sensitive with UV light. The photosensitive film was irradiated by laser interference of THG Nd-YAG laser (λ = 355 nm) yield 2D grating with hexagonal structure. The characteristic of lasing was investigated using strip-line excitation light of SHG Nd-YAG laser (λ = 532 nm). The lasing wavelengths are observed at 606 and 621 nm for grating period of 400 and 410 nm, respectively. The spectral width (FWHM) of lasing is about 3 nm at pumping power 14.88 mJ/pulse cm2.